Characterisation of lemon-flavoured olive oils. (June 2017) - Sacchi, Raffaele; Della Medaglia, Dorotea; Paduano, Antonello; Caporaso, Nicola; Genovese, Alessandro
Abstract: Fresh lemons ( Citrus limon L.) from two locations in Italy were added to fresh olives before milling them to produce flavoured olive oils (FOO). FOOs were characterized for their quality parameters, fatty acid composition, biophenol content, volatile compound composition and sensory profile. Sensory results showed that lemon volatiles would mask negative notes of olive oil obtained from olives with slight off-flavours by adding strong notes of lemon leaf, albedo and lemon juice, while they decreased the positive notes of olive fruit, green, leaf and bitter-pungent from good quality olives. Flavouring OO with lemon significantly affected quality indices, with a significant increase of the acidity value and UV indices. OO flavouring with fresh lemon also affected the phenolic compounds, particularly the simplest forms, hydroxytyrosol and tyrosol. A dramatic decrease of the concentration of aldehydic and dialdehydic forms of oleuropein was also observed in FOO. As expected, volatile profile of virgin OO dramatically changed due to lemons addition, which caused the presence of several terpene compounds, namely limonene, α-pinene, β-pinene, sabinene, β-mircene and γ-terpinene. In contrast, virgin OO volatile compounds decreased with lemon addition. In conclusion, addition of lemon to OO should be carried out by considering these results, as well as the legislation for this kind of product. Graphical abstract: Highlights: Flavoured olive oil produced by direct addition of lemon in the mill was studied. Changes in quality indices, phenolics, volatiles and sensory scores were found. Addition of lemon caused a decrease in acidity and other quality parameters. Olive oil biophenol concentration decreased significantly in flavoured oils. Abundant lemon terpene levels covered the typical virgin olive oil sensory notes.